Cross-Talk Between Thyroid Disorders and Nonalcoholic Fatty Liver Disease: From Pathophysiology to Therapeutics - Yang, Yan; Xiao, Jiyuan; Qiu, Wen; Jiang, Luxia (Hormone and Metabolic Research, 2024)
The medical community acknowledges the presence of thyroid disorders and nonalcoholic fatty liver disease (NAFLD). Nevertheless, the interconnection between these two circumstances is complex. Thyroid hormones (THs), including triiodothyronine (T3) and thyroxine (T4), and thyroid-stimulating hormone (TSH), are essential for maintaining metabolic balance and controlling the metabolism of lipids and carbohydrates. The therapeutic potential of THs, especially those that target the TRβ receptor isoform, is generating increasing interest. The review explores the pathophysiology of these disorders, specifically examining the impact of THs on the metabolism of lipids in the liver. The purpose of this review is to offer a thorough analysis of the correlation between thyroid disorders and NAFLD, as well as suggest potential therapeutic approaches for the future.
Keywords: thyroid disorders; NAFLD; pathophysiology; therapeutics